2019
DOI: 10.1101/627687
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantitative evaluation of a high resolution lipidomics platform

Abstract: Given the general importance of lipids in health and disease, there is a need for efficient technology that broadly profiles and quantitates the lipid composition of complex mixtures.In this study, we developed and quantitatively evaluated a platform that simultaneously profiles both lipids and polar metabolites from the same sample. This method was achieved by using a methyl tert-butyl ether (MTBE) extraction and employing two liquid chromatography methods coupled with high resolution mass spectrometry (LC-HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Therefore, the recorded changes in respective metabolite concentrations can serve as a readout of cellular biochemical activity and its response to changes in the environment. Hence, an approach to extract and measure the broadest possible range of lipids and polar metabolites in human plasma is fundamental for better understanding of metabolic changes in different physiological conditions [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the recorded changes in respective metabolite concentrations can serve as a readout of cellular biochemical activity and its response to changes in the environment. Hence, an approach to extract and measure the broadest possible range of lipids and polar metabolites in human plasma is fundamental for better understanding of metabolic changes in different physiological conditions [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The methyl tert-butyl ether (MTBE)-methanol-water liquid-liquid extraction (LLE) method for lipid extraction developed by Matyash et al (14)(15)(16) has been demonstrated to have similar performance to the chloroform-based method developed by Folch (17), but with the advantages of avoiding chlorinated solvents and locating the protein pellet at the bottom of the vessel, making it a popular alternative to chloroform-based extractions for lipidomics. There are several reports of metabolomics analysis on the aqueous phase of this preparation in conjunction with lipidomics analysis of the organic phase (18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%